The undoing project [large type] : a friendship that changed our minds - Lewis, Michael (Michael M.) (Thorndike Press, 2017)
"Forty years ago, Israeli psychologists Daniel Kahneman and Amos Tversky wrote a series of breathtakingly original studies undoing our assumptions about decision-making, showing the ways in which the human mind systematically erred when forced to make judgments about uncertain situations. They are largely responsible for the powerful trend to mistrust human intuition and defer to algorithms. The Undoing Project is about the fascinating collaborations between two men who may well have changed, for good, mankind's view of its own mind." -- Back cover.